THE INFLUENCE OF LEARNING STYLES AND MOTIVATION OF CLASS XI STUDENTS ON THE EFFECTIVENESS OF DIFFERENTIATED GEOGRAPHY LEARNING AT SMA NEGERI 3 HALMAHERA UTARA, INDONESIA - Elvis Awa; Roni Alim Ba'diya Kusufa; Ninik Indawati; Dwi Fauzia Putra (Universitas Negeri Surabaya, 2026)
This study analyzes the influence of students’ learning styles and learning motivation on the effectiveness of differentiated Geography learning at SMA Negeri 3 Halmahera Utara. This study is based on the importance of differentiated learning in accommodating students’ learning characteristics in the context of an archipelago with diverse geographical conditions. A quantitative approach with an explanatory method was used involving 61 students. Data were collected through a closed questionnaire through validity and reliability tests. Data analysis used a t-test. The results showed that learning styles have a significant influence on the effectiveness of differentiated learning, with a t-value of 10.786 and a learning motivation t-value of 7.228, with a coefficient of determination of 47.0%. These findings confirm that differentiated learning based on student characteristics and local environmental conditions increases student engagement, learning effectiveness, and contextual relevance in Geography education. Keywords: Learning Styles, Learning Motivation, Differentiated Instruction